MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAPAT MENINGKATKAN HASIL BELAJAR SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU - ObajaDwi Handoko (Journal for Lesson and Learning Studies, 2018)
This study has a purpose to describe the steps of using Problem Based Learning model, in improving learning outcomes Subtheme Curtural Diversity in My Country. The research was conducted in SD Negeri Purwosari 01 Temanggung Regency with the subject of research is the fourth grader of SD Negeri Purwosari 01. The independent variable in this research is the learning model of Problem Based Learning, while the dependent variable, that is student learning outcomes. Data collection by observation and test. this study is designed to be implemented in two cycles. This study is designed to be implemented in two cycles. Each cycle consists of four stages: planning, action, observation, and analysis and reflection. Data analysis techniques in this study are divided into two, the first is the analysis of quantitative data, is the value of student learning outcomes, and the second is the qualitative data, sentences that describe the results of observations on the implementation of learning. The results showed that the application of Problem Based Learning model can improve student learning outcomes. The analysis of learning result data shows that students' learning completeness is only 23.08%, increased to 46.15% in cycle I and in cycle II the learning completeness has reached 92.31%. Keyword : Problem Based Learning, Learning Result